Do hotel facilities matter for the customer? Analyzing the impact of risk perception toward guest satisfaction mediated by accommodation attributes in the hospitality industry - Maulana, Noveri (Journal of Tourism Management Research, 2024)
This study aims to analyze the relationship between risk perception variables and guest satisfaction mediated by hotel attributes in the hospitality industry in Indonesia. Previous studies argued that guest preference toward hotel attributes can mediate the impact of risk perception toward guest satisfaction when staying at an accommodation. However, some other findings contrast this argument. This study aims to contribute to these theoretical debates among the scholars. As a quantitative study, data were collected through a field survey of 568 foreign and domestic tourists in major tourist destinations in Indonesia. The SEM-PLS with bootstrapping analysis for mediation effect was applied in the study. The result reveals that financial risk does not directly influence guest satisfaction but significantly affects hotel attribute preferences. Health risk similarly impacts hotel attribute preferences positively without directly affecting guest satisfaction. Conversely, psychosocial risk exhibits a strong negative effect on guest satisfaction and hotel attributes. The positive relationship between hotel attributes and guest satisfaction reaffirms the critical role of service quality and physical attributes in driver satisfaction. Mediation analysis indicates that hotel attributes significantly mediate the effects of risk factors on guest satisfaction. The study concludes that enhancing hotel attributes, addressing psychosocial concerns, and investing in health-related features are pivotal strategies for hotel management to boost guest satisfaction, particularly during periods of heightened financial and health risks. These findings offer valuable insights for hotel managers to navigate challenging times and maintain high levels of guest satisfaction, fostering loyalty and positive word-of-mouth among the tourists.